2003
DOI: 10.2527/2003.8181959x
|View full text |Cite
|
Sign up to set email alerts
|

A gonadotropin-releasing factor vaccine (Improvac) and porcine somatotropin have synergistic and additive effects on growth performance in group-housed boars and gilts1,2

Abstract: Two hundred and twenty-four pigs (112 boars, 112 gilts) housed in pens of seven pigs per pen were used in a 2 x 2 x 2 factorial design, with the factors of vaccination with a gonadotropin-releasing factor (GnRF) vaccine (Improvac; 0 or 2 mL at 13 and 17 wk of age), porcine somatotropin (pST; 0 or 5 mg/d from 17 wk of age), and gender. Pigs were weighed and feed intake was measured from 17 wk of age until slaughter at 21 wk of age. Body composition was estimated by dual-energy X-ray absorptiometry in two focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
35
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 10 publications
14
35
0
6
Order By: Relevance
“…Carcass quality It has been reported that immunocastration of gilts increased carcass fatness (Oliver et al, 2003), which is confirmed by the present data. Serrano et al (2008) also observed that surgical castration of gilts increased subcutaneous fat thickness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Carcass quality It has been reported that immunocastration of gilts increased carcass fatness (Oliver et al, 2003), which is confirmed by the present data. Serrano et al (2008) also observed that surgical castration of gilts increased subcutaneous fat thickness.…”
Section: Discussionsupporting
confidence: 92%
“…There is scarce information in the literature about immunocastration in gilts or comparing immunocastrated and surgically castrated gilts. Oliver et al (2003) found that immunocastration led to a reduction in ovary weight and an increase in daily BW gain and feed intake. In a recent study, Gómez-Fernández et al (2013) observed that Duroc × Iberian IG had higher ADG, ADFI and FCR than EG.…”
Section: Discussionmentioning
confidence: 98%
“…Immunization against GnRF is an alternative method of inhibiting sexual Nutritional requirements of anti-GnRF immunized boars 1771 development and aggressive behaviours in the late finisher phase and reducing the accumulation of boar taint compounds in carcass fat. This results in a reduction in plasma gonadotrophins and testosterone (Bonneau et al, 1994;Dunshea et al, 2001;McCauley et al, 2003;Oliver et al, 2003). The reduction in testosterone as a result of immunization against GnRF has a profound effect upon behaviour (Rydhmer et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Australia) and comparisons have been made with entire males. An experiment conducted by Oliver et al (2003) gives interesting indications concerning the performance of immunocastrates and entire males, although its aim was to determine the consequence of the use of Improvac R combined with daily injections of porcine somatropin.…”
Section: Immunocastrationmentioning
confidence: 99%